Development of Unilateral Peri-Lead Edema Into Large Cystic Cavitation After Deep Brain Stimulation: A Case Report - Lu, Yue; Qiu, Chang; Chang, Lei; Luo, Bei; Dong, Wenwen; Zhang, Wenbin; Sun, Hai-Hua (Frontiers in Neurology, 2022)
Background and Importance Deep brain stimulation (DBS) has been approved to treat a variety of movement disorders, including Parkinson's disease (PD), essential tremor, and dystonia. Following the DBS surgery, some perioperative and even delayed complications due to intracranial and hardware-related events could occur, which may be life-threatening and require immediate remedial measures. Clinical Presentation We report a case of an older woman with advanced PD who developed the unique complication of unilateral cyst formation at the tip of the DBS electrode after undergoing bilateral placement of subthalamic nucleus DBS. After a period of controlled motor symptoms, the patient showed new neurological deficits related to right peri-lead edema. However, the new neurological symptoms regressed quickly over several days with stereotactic implantation of a puncture needle to drain the cyst fluid without removing the affected lead. Conclusion The occurrence of an intraparenchymal cyst following DBS surgery is a rare but life-threatening complication that could relate to edema around the electrodes or cerebrospinal fluid tracking. Stereotactic aspiration makes the intracranial cyst regress safely and effectively and ensures that the electrode is in the optimal position of the target nucleus to achieve an effective DBS surgery.